Peran Guru dalam Meningkatkan Religiusitas Siswa di SD Integral Hidayatullah Probolinggo - Hanina Maria Ulfa (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Islamic Religious Education is the most important component in life, acting as a foundation for thinking, acting, and behaving, both in the family and community environment. This study aims to analyze the role of teachers in improving student religiosity at SD Integral Hidayatullah Probolinggo, with a focus on the approach to religious education, the application of religious values ​​in daily activities, and positive habits. As a school that implements the full-day school concept. This study uses a qualitative descriptive approach method with triangulation techniques, namely participatory observation of the school environment studied, in-depth interviews, and documentation of the research background, then analyzed using the Miles and Huberman theory, namely: data reduction, data display, and conclusion drawing/verification. This study found that teachers have a central role in instilling religious values ​​through exemplary methods, interactive discussions, and routine activities, such as joint prayer and congregational prayer. In addition, this success is supported by adequate school facilities and an integrative curriculum that supports the teaching of religious values. However, the study also identified several obstacles, including the lack of support from students' families in continuing religious habits at home and the density of the academic curriculum. This shows the importance of synergy between schools, teachers, and families to create an environment that supports the continuous improvement of student religiosity. Thus, through increased collaboration between related parties, schools can be more optimal in achieving their goals of producing a generation with noble morals, faith, and strong character.